Clinical evaluation of near-infrared light transillumination (NIRT) as an interproximal caries detection tool in a large sample of patients in a private practice. Issue 1 (2016) - Russotto, Francesco; Tirone, Federico; Salzano, Stefano; Borga, Francesco Coero; Paolino, Davide; Ferraro, Alberto; Botasso, Samanta
No abstract available